Concepts of soul : an investigation into the concepts of the soul current at the inception of Christianity - Rawetzky, Greta (Department of Religious Studies, 2015)
This thesis has been called forth by the debate about the concept soul which has been pursued in many fields: in theology by Oscar Cullmann and many others; in philosophy by Gilbert Ryle, among others. In psychology, we find that as early as 1926, at an International Psychological Conference, Pavlov declared that we must abandon the misleading term "soul". He stated that, in his opinion, "the proper study of psychology is physiology".